The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3122/jabfm.2019.05.190026
|View full text |Cite
|
Sign up to set email alerts
|

Visit Entropy Associated with Diabetic Control Outcomes

Abstract: Background: Chronic diseases such as type 2 diabetes place a large burden on the health care system and are associated with increased morbidity and mortality. A team-based multidisciplinary approach that organizes care to improve chronic disease management may actually decrease traditional continuity of care metrics. Visit entropy (VE) provides a novel measure of care organization produced by teambased approaches. Higher VE, reflecting more disorganized care, has been associated with more hospital readmissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…We also note that the approach we have used has potential applications for other fragmentation measures. For example, recent studies have examined “visit entropy” using a measure closely related to entropy statistics from population genetics that have been studied in a similar way to the analogues of UPC and COCI . Examining the mathematical relationship between UPC and visit entropy could further shed light on the distinct contributions of different measures and combinations of measures.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the approach we have used has potential applications for other fragmentation measures. For example, recent studies have examined “visit entropy” using a measure closely related to entropy statistics from population genetics that have been studied in a similar way to the analogues of UPC and COCI . Examining the mathematical relationship between UPC and visit entropy could further shed light on the distinct contributions of different measures and combinations of measures.…”
Section: Discussionmentioning
confidence: 99%
“…Put another way, disorganized care is as important as the history of myocardial infarction, congestive heart failure, chronic obstructive pulmonary disease, or diabetes without end‐organ damage to hospital readmission risk. Likewise, Dilger et al showed, higher VE is associated with reduced odds of meeting diabetic quality metrics (OR = 0.88) 21 . Their study showed that a single unit increase in disorganized care (equivalent to seeing three different physicians vs seeing the same primary physician three times) as measured by VE produces a 47% lower probability of a controlled D5 metric (a1c < 8.0, blood pressure < 140/90, on statin, non‐smoker, on anti‐platelet agent).…”
Section: Figurementioning
confidence: 99%
“…In fact, almost half of primary care patients do not visit their primary care physician's office in a given year 19 . This results in a division by zero error making the calculation of these indexes undefined, often resulting in the elimination of significant number of patients from studies 15,20,21 . The problem is worse for COC and SECON which require at least two visits.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The other original research articles in this issue remind us that not all practice-based research takes place in PBRNs. Using EHR data from 5 practices, Dilger et al 16 posit that visit entropy is a better measure of care organization and is associated with better diabetic quality scores. And reporting on just a single practice, Morcos 17 presents compelling evidence for the importance of taking the blood pressure the right way in daily office practice, an oftenoverlooked component of quality care.…”
Section: Not All Practice-based Research Takes Place In Pbrnsmentioning
confidence: 99%